2020
DOI: 10.1088/1741-2552/abc025
|View full text |Cite
|
Sign up to set email alerts
|

Long-term performance of Utah slanted electrode arrays and intramuscular electromyographic leads implanted chronically in human arm nerves and muscles

Abstract: Objective. We explore the long-term performance and stability of seven percutaneous Utah Slanted Electrode Arrays (USEAs) and intramuscular recording leads (iEMGs) implanted chronically in the residual arm nerves and muscles of three human participants as a means to permanently restore sensorimotor function after transradial amputations. Approach. We quantify the number of functional recording and functional stimulating electrodes over time. We also calculate the signal-to-noise ratio (SNR) of USEA and iEMG re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…The impedance of the electrodes and stimulation thresholds did not change by more than 20% over time. While the duration of this study was limited to 6-months, UEAs have been successfully implanted in human subjects in numerous studies (25)(26)(27)(28)(29), and these devices have continued to work for many years. A recent systematic review of human neuroprosthetic research using the UEA reported that the mean number of days of UEA implantation across all participants at the time of the study was at least 578 days (30), and several studies indicate that Utah Electrode Arrays retain their functionality in human for more than 1000 days (29,31).…”
Section: Discussionmentioning
confidence: 99%
“…The impedance of the electrodes and stimulation thresholds did not change by more than 20% over time. While the duration of this study was limited to 6-months, UEAs have been successfully implanted in human subjects in numerous studies (25)(26)(27)(28)(29), and these devices have continued to work for many years. A recent systematic review of human neuroprosthetic research using the UEA reported that the mean number of days of UEA implantation across all participants at the time of the study was at least 578 days (30), and several studies indicate that Utah Electrode Arrays retain their functionality in human for more than 1000 days (29,31).…”
Section: Discussionmentioning
confidence: 99%
“…The intensity was used to find the perceptual thresholds for each stimulation channel ( 4 , 23 , 24 , 31 ), together with the range of stimulation (between threshold and below pain level). Using a VAS scale in the range from 0 to 10 also enables us to identify perceptual magnitude levels ( 5 , 23 , 32 , 52 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, to provide a rich and reliable artificial sensory feedback to the patient, it is necessary to accurately test multiple sets of stimulation parameters and re-test them even over multiple days during long-term applications (14,(30)(31)(32)(33). This characterization procedure is fundamental to re-create an artificial sensory feedback that could be effectively exploitable in neuroprosthetic applications by the users.…”
Section: Introductionmentioning
confidence: 99%
“…EMG signals in addition to the ENG signals were required to achieve this level of control (Wendelken et al, 2017 ). Though signals tend to degrade over time, performance of USEAs continue to improve with recent evidence of stability and functionality after 14 months (George et al, 2020 ). These electrodes are capable of recording and stimulating individual neural fascicles and thus have the potential to provide complex control of a prosthesis.…”
Section: Electrodesmentioning
confidence: 99%